An Evaluation of Irrational Drug Consumption in Shiraz Households in 2019 - Zahra Kavousi; Shima Bordbar; Saeideh Negahdari; Mostafa Ghaeminia; Seyede Neda Shahghasemi (علوم بهداشتی ایران, 2022)
Background: Medical experts believe that proper use of medicine in many cases results in the treatment of the disease. This study was conducted to determine the rate of irrational drug use in households in Shiraz in 2019. The criteria for rationality of drug use were as follows: 1. Using medicine for the existing disease- 2. Preparing medicine by visiting a doctor- 3. Appropriate storage location- 4. Unexpired drug- 5. Proper drug use. Methods: This study was a cross-sectional household survey conducted using a descriptive questionnaire based on the drug survey plan questionnaire in Oman by stratified random sampling. 156 households were surveyed. Data analysis was performed by t-test , ANOVA, Pearson Correlation Coefficients and chi-square tests using SPSS-22 software. Results: Out of 1944 items of medicine available in households, 542 items (27.9%) were used rationally and 1402 items (72.1%) were used or stored irrationally. Among the available drug categories, drugs related to cancer (80%) and heart (75.2%) disease had the highest rational use. Skin drugs (0%) and antibiotics (8.3%) had the most irrational use. There was also found a significant relationship between the rational consumption and the region where households lived (P-value≤0/001) (municipal regions), rational consumption and drug literacy for each drug, as well as rational consumption and how the drug was prepared (P-value ≤ 0/001). Conclusion: Based on the research findings, it was found that in most households, drugs were accumulated irrationally. The high dispersion of medicine stored in households indicated the diversity and lack of a correct and coherent culture for consuming medicine among citizens and prescribing it among the medical community in Shiraz. It was then suggested that through more detailed educational planning, the health system and corresponding officials improve the pattern of drug use as well as its prescription. Furthermore, increasing people's awareness of how to use and maintain medicines can reduce their expenses.